Interactions of corneal cells with transforming growth factor-beta modified poly(dimethyl siloxane) surfaces. - Merrett, Kim. (University of Ottawa (Canada), 2002)
Although the growth of native corneal epithelial cells over the anterior surface of an artificial corneal implant is desired, the growth of these cells on the interface located between the implant and the stromal layer of the host eye tissue (i.e. epithelial cell downgrowth) poses a significant problem to be overcome in developing a suitable implant. In this study the growth factor surface modification of a polymer substrate was examined as a means of inhibiting the proliferation of corneal epithelial cells while promoting corneal stromal cell growth. Two separate studies were conducted in which transforming growth factor-beta1 (TGF-beta1) and transforming growth factor-beta2 (TGF-beta2) respectively, were immobilized via a bifunctional poly (ethylene glycol) (PEG) spacer, MW 3400, to poly(dimethyl siloxane) surfaces (PDMS) that had been aminated by the plasma polymerization of allylamine. The modified surfaces were chemically and biologically characterized. The effect of the surface modification with TGF-beta1 and TGF-beta2 respectively, on interactions with corneal epithelial and corneal stromal cells was examined using in vitro cell culture. (Abstract shortened by UMI.)
Keywords: Biology, Cell.